Analgesic and anti-inflammatory activity of ethanolic extracts of leaf and fruit pulp of Aegle marmelos in albino rats - K., Krishnakanth; B. G., Abhilash; K., Neeraja; Rao G., Hari Jagannadha; Cheekavolu, Chakrapani (International Journal of Basic & Clinical Pharmacology, 2017)
Background: To study the analgesic and anti-inflammatory activity of the ethanolic extracts of leaf (LE) and fruit pulp (FE) of Aegle marmelos in comparison with the standard drugs pentazocine and diclofenac in albino rats. 56 healthy wistar albino rats of either sex were randomly divided into 14 groups of 4 each (n=4), weighing about 150-200grams were selected for the study. All drugs i.e. 1ml of 1% Carboxy methyl cellulose (CMC), pentazocine 10mg/kg (intraperitoneal), diclofenac 10 mg/kg and LE and FE at doses of 100mg/kg and 200mg/kg in 1% CMC (vehicle) were administered per oral one hour before the experiment. Methods: Analgesic activity was assessed by Eddy’s hot plate method (latency time) and acetic acid induced writhing (number of writhings) method. Anti-inflammatory activity was assessed by carrageenan induced hind paw edema method using digital plethysmometer. Results: Test drugs at doses LE 200mg/kg and FE 200mg/kg have shown significant increase in mean latency time in Eddy’s hot plate (P <0.001) and decrease in the average number of writhing movements (P <0.01). LE 200 and FE 200 doses did not show significant anti-inflammatory activity in Carrageenan induced paw edema model (P >0.05). Conclusions: Leaf extract (LE) and fruit extract (FE) at doses 200mg/kg have shown significant analgesic action and no anti-inflammatory action.